Electrophysiological Changes in Children with Isolated Persistent Left Superior Vena Cava: A Case–Control Study - Sule Arici; Ozlem Surekli Karakus; Gulperi Yagar Keskin; Erkan Tas; Fatih Alparslan Genc; Sezin Bayraktar; Metin Sungur; Ayse Inci Yildirim (Journal of Clinical Medicine, 2026)
Background: Persistent left superior vena cava (PLSVC) is the most common congenital anomaly of the thoracic venous system and is generally considered a benign variant. This study aimed to evaluate arrhythmia-related electrocardiographic parameters in children with isolated PLSVC and to assess the relationship with coronary sinus dimensions. Methods: This retrospective cross-sectional study included 26 children with isolated PLSVC and 26 age- and sex-matched healthy controls. All participants underwent transthoracic echocardiography and electrocardiographic analysis. Coronary sinus diameters were measured and indexed to body surface area. Electrocardiographic parameters reflecting atrial conduction and ventricular repolarization heterogeneity, including P-wave dispersion, QTc dispersion, Tp–e interval, and indices of cardiac electrophysiological balance (QT/QRS and QTc/QRS), were evaluated. Results: P-wave dispersion (62.15 ± 14.78 vs. 35.59 ± 10.02 ms, p < 0.001), QTc dispersion (99.66 ± 30.10 vs. 40.45 ± 10.78 ms, p < 0.001), and Tp–e dispersion (67.29 ± 19.10 vs. 38.42 ± 7.13 ms, p < 0.001) were significantly higher in the PLSVC group. QT/QRS (4.33 ± 0.59 vs. 3.78 ± 0.36, p < 0.001) and QTc/QRS (5.48 ± 0.91 vs. 4.61 ± 0.36, p < 0.001) ratios were also increased. Coronary sinus measurements showed weak and inconsistent correlations with electrocardiographic parameters. Conclusions: Children with isolated PLSVC exhibit significant electrocardiographic alterations reflecting atrial and ventricular electrical heterogeneity. These findings suggest that PLSVC may be associated with subclinical electrophysiological abnormalities beyond a benign anatomical variant. Accordingly, increasing clinical awareness of potential arrhythmic risk during follow-up and considering this aspect in patient evaluation may be appropriate.